Honneth and Everyday Intercultural (Mis)Recognition Work, Marginalisation and Integration - Anna, Bona (Palgrave Politics of Identity and Citizenship Series, 2018)
This book conducts a critical investigation into everyday intercultural recognition and misrecognition in the domain of paid work, utilising social philosopher Axel Honneth's recognition theory as its theoretical foundation. In so doing, it also reveals the sophistication and productivity of Honneth's recognition model for multiculturalism scholarship. Honneth and Everyday Intercultural (Mis)Recognition is concerned with the redress of intercultural related injustice and, more widely, the effective integration of ethically and culturally diverse societies. Bona Anna analyses the everyday experiences of cross-cultural misrecognition in a distinctive ethno-cultural group, including social norms that have been marginalised in the contexts of employment. In this endeavour, she deploys key constructs from Honneth's theory to argue for individual and social integration to be conceptualised as a process of inclusion through stables forms of recognition, rather than as a process of inclusion through forms of group representation and participation. This book will appeal to students and academics of multiculturalism interested in learning more about the usefulness of Honneth's recognition theory in intercultural inquiry, including the ways in which it can circumvent some of the impasses of classical multiculturalism.